2019
DOI: 10.21203/rs.2.15721/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment and Validation of a Nomogram with Intratumoral Heterogeneity Derived from 18F-FDG PET/CT for Predicting Individual Conditional Risk of 5-Year Recurrence before Initial Treatment of Nasopharyngeal Carcinoma

Abstract: Objectives Intratumoral heterogeneity has an enormous effect on patient treatment and outcome. The purpose of the current study was to establish and validate a nomogram with intratumoral heterogeneity derived from 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for prognosis of 5-Year progression-free survival (PFS) of patients with nasopharyngeal carcinoma (NPC).Methods A total of 171 NPC patients who underwent pretreatment 18F-FDG PET/CT were retrospectively enrolled. D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Radiomic features from [ 18 F]FDG-PET/CT images can quantify the spatial heterogeneity of tumors and have become potential prognostic predictors of many diseases [28][29][30][31]. However, as [ 18 F]FDG PET/CT radiomics has not been widely applied to predict the clinical prognosis of cancer cases, there is no consensus on the screening of texture features [28].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic features from [ 18 F]FDG-PET/CT images can quantify the spatial heterogeneity of tumors and have become potential prognostic predictors of many diseases [28][29][30][31]. However, as [ 18 F]FDG PET/CT radiomics has not been widely applied to predict the clinical prognosis of cancer cases, there is no consensus on the screening of texture features [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although it provided a better predictive efficacy, there is still a long way to go before clinical application because of constraints in the instability of MRI-based radiomics. Compared with previous prognostic models [26,27], a major strength of our model is that prognostic factors were easy to obtain, and the nomogram yielded a satisfactory C-index as well.…”
Section: Consistent With the Conclusion N Category Has Comparable Prmentioning
confidence: 95%
“…PET-computed tomography (PET/CT) using fluorine-18 fludeoxyglucose ( 18 F-FDG) provides high spatial resolution and semiquantitative parameters. It is a widely used technique for NPC staging assessment and prediction of clinical outcomes [4][5][6]. Gu et al [6] analyzed the clinicopathologic parameters and some PET parameters from pretreatment 18 F-FDG PET/CT images of 171 patients with NPC and constructed a prognostic nomogram.…”
Section: Introductionmentioning
confidence: 99%
“…It is a widely used technique for NPC staging assessment and prediction of clinical outcomes [4][5][6]. Gu et al [6] analyzed the clinicopathologic parameters and some PET parameters from pretreatment 18 F-FDG PET/CT images of 171 patients with NPC and constructed a prognostic nomogram. It has shown that intratumor heterogeneity can predict the long-term prognosis of patients with NPC.…”
Section: Introductionmentioning
confidence: 99%